2021
DOI: 10.3390/molecules26061530
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Phenolic Compound Profile and Antioxidant Potential of Achillea atrata L. and Achillea millefolium L.

Abstract: In the present study, Achillea atrata L. and A. millefolium L. were compared for the first time with regard to their phenolic compound profile and antioxidant activity by applying the 2,2-diphenyl-picryl hydrazyl radical assay. For this purpose, aerial plant parts were consecutively extracted with solvents of increasing polarity (dichloromethane, n-butanol, ethyl acetate), revealing that the A. atrata ethyl acetate fraction showed the highest antioxidant activity with an IC50 value of 12.2 ± 0.29 µg/mL compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Chemical characterization of MeOH, EtOH, or aqueous A. millefolium extracts confirmed the presence of various bioactive compounds, dominated by chlorogenic acid, isomers of dicaffeoylquinic acids, and flavonoids [7,14,17,51]. In our particular case, seven different phenolic compounds were identified by HPLC-MS and HPLC-UV, quantified in all of the obtained extracts (Figure 2 and Table 2).…”
Section: Extraction Of the Phenolic Compounds Of A Millefolium With N...mentioning
confidence: 53%
See 1 more Smart Citation
“…Chemical characterization of MeOH, EtOH, or aqueous A. millefolium extracts confirmed the presence of various bioactive compounds, dominated by chlorogenic acid, isomers of dicaffeoylquinic acids, and flavonoids [7,14,17,51]. In our particular case, seven different phenolic compounds were identified by HPLC-MS and HPLC-UV, quantified in all of the obtained extracts (Figure 2 and Table 2).…”
Section: Extraction Of the Phenolic Compounds Of A Millefolium With N...mentioning
confidence: 53%
“…Although the antioxidant properties of A. millefolium have been evaluated previously and reported [7,14,16,17,51], a direct comparison of the results is difficult due to the different ways in which the results are expressed by the authors. For example, Vladić et al reported an ABTS value of 1730.84 µg TE mL −1 under the optimized SWE extraction conditions (temperature 198 • C, extraction time 16.5 min, and without acidifier) [17], while Villalva et al determined an ABTS value of 0.345 ± 0.002 mmol TE g −1 for the extract obtained by supercritical anti-solvent fractionation (SAF) [7].…”
Section: Extraction Of the Phenolic Compounds Of A Millefolium With N...mentioning
confidence: 99%
“…Two flavones bearing a methoxy group attached to C-7 or C-3 were reported once, namely 7-O-methyl apigenin (3) (from A. ligustica) [35] and chrysoeriol (20) (from A. millefolium) [40], respectively. Moreover, other methylated flavonoids, such as cirsiliol (22) and cirsimaritin (4), were reported for A. fragrantissima [31,33]; salvigenin (5) for A. millefolium [41] and A. wilhelmsi [50]; and 8-hydroxysalvigenin (6) was identified for A. lycaonica A. monocephala and A. vermicularis [36,42,49]. Moreover, eupatorin (21) was reported for A. alpina and A. tenuifolia [17,48], while eupatilin 7-methyl ether (5-demethylsinensetin) (23) for A. wilhelmsii [25].…”
Section: Flavonoidsmentioning
confidence: 99%
“…More precisely, decoctions of this plant were used to treat arthritis, cardiovascular diseases, congestions, gastrointestinal disorders, gout, and malaria, and as a diuretic, anthelmintic, and purgative agent [79]. Antioxidant and antimicrobial effects have been reported for this plant [22,105].…”
Section: Ethnopharmacological Relevance: Traditional Uses Of the Genu...mentioning
confidence: 99%
See 1 more Smart Citation